Surgical treatment of diabetic macular edema - R. R. Fayzrakhmanov; O. A. Pavlovsky; M. A. Lukinykh; N. S. Egorova (Российский офтальмологический журнал, 2024)
Diabetic retinopathy (DR) and diabetic macular edema (DME) present a serious medical and social issue of modern society. DME is one of the most common complications of DR and a frequent cause of a sudden decrease in visual acuity and the onset of disability. The review describes the main links of DME pathogenesis, including the participation of inflammatory cytokines, glycation products, reactive oxygen species, vascular endothelial growth factor and various cellular damages. The existing classifications of the disease, instrumental methods of diagnosis and treatment are presented, primarily those using angiogenesis inhibitors alone or in combination with laser treatment and intravitreal injection of an implant with dexamethasone. Various methods of surgical treatment of DR, which can impact the course of DME, are analyzed, including vitreoretinal surgery using vitrectomy with or without membrane peeling of the internal limiting and epiretinal membranes. Factors predicting the effectiveness of these surgical interventions are listed: these can be based on the general somatic condition of the patient and on the results of optical coherence tomography.